Politics and Celebration: Manifesting the Rainbow Flag - Hagen-Smith, Lisa (Ethnologies, 1997)
Traditionally, organizers of the Winnipeg Lesbian, Gay, Bi PRIDE Day event have constructed two arenas (The Social and The March) which separate and contain expressions of celebration and protest. In 1996, Winnipeg organizers created a third space for the festival between these two spaces. Organizers also consciously began the transition from March to Parade. This paper discusses ways in which rainbow symbolism mediates the tensions between protest and celebration. Whether in its original form as flag or in its various manifestations, rainbow symbolism creates and daims various sites of conflict, transformation and inspiration. The meaning created by its use sometimes privileges celebration, other times protest and occasionally, magically transforms the space into a hybrid of both. Using the concepts of syndesis and synthesis I explore the strategic nature of this culturally significant symbol. It has only recently been collectively adopted by gay, lesbian and bisexual Manitobans and therefore, although well established in the United States, locally, it represents an emergent communication of pride.